Вплив умов праці в гірничо-металургійній галузі України на ризик розвитку захворювань з тимчасовою втратою працездатності = The impact of working conditions in mining and metallurgical industry of Ukraine at the risk of development of diseases with the temporary disability - Oriekhova, O. V. (Journal of Education, Health and Sport, 2016)
Oriekhova O. V. Вплив умов праці в гірничо-металургійній галузі України на ризик розвитку захворювань з тимчасовою втратою працездатності = The impact of working conditions in mining and metallurgical industry of Ukraine at the risk of development of diseases with the temporary disability. Journal of Education, Health and Sport. 2016;6(7):173-186. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57304 http://ojs.ukw.edu.pl/index.php/johs/article/view/3687 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.06.2016. Revised 09.07.2016. Accepted: 09.07.2016. УДК 613.62+614.29] 622 + 669 Вплив умов праці в гірничо-металургійній галузі України на ризик розвитку захворювань з тимчасовою втратою працездатності О. В. Орєхова Український науково-дослідний інститут промислової медицини м. Кривий Ріг, Україна Реферат Проведено поглиблений аналіз захворюваності з тимчасовою втратою працездатності для встановлення достовірно доведеного причино-наслідкового зв’язку між станом здоров'я працюючих та виробничо-професійними умовами з метою розробки, впровадження та контролю ефективності профілактичних заходів, які направлені на зниження захворюваності та керування професійним ризиком. Зниження рівня захворюваності має не лише соціальне, а й економічне значення, тому що сприяє збереженню у сфері виробництва значної кількості працівників. Встановлено, що ризик розвитку загальних захворювань у працівників гірничо-металургійної галузі є нижче, ніж у контрольній групі та становить 0,127 для підземного видобутку залізної руди, 0,173 для відкритого видобутку залізної руди та 0,161 для металургійного виробництва, а відношення шансів захворіти на професійне захворювання (OR) становить 0,0516, 0,041 та 0,0061 відповідно, що корелює з умовами праці. При розрахунку показників ЗТВП встановлено, що умови праці для підземного і відкритого видобутку залізної руди відповідають 3 класу 2 ступеня шкідливості, а для металургійного виробництва – 3 класу 1 ступеня шкідливості або допустимому. Обґрунтовано та доведено, що поглиблений аналіз захворюваності та встановлення причин, що призводять до її збільшення дозволить проводити динамічний нагляд, моніторинг за станом здоров’я кожного конкретного працівника з метою своєчасного виявлення початкових проявів професійного захворювання та обов’язкового проведення відновлювального лікування з метою збереження працездатності працівника у своїй професії, розрахунок індивідуального безпечного терміну роботи та відкриють перспективи для подальших наукових досліджень, спрямованих на розроблення та впровадження ефективної системи керування професійним ризиком. Ключові слова: поглиблений аналіз захворюванності, ймовірність захворіти, виробничо-професійні умови, стан здоров’я, доведений причинно-наслідковий зв’язок. The impact of working conditions in mining and metallurgical industry of Ukraine at the risk of development of diseases with the temporary disability O. V. Oriekhova Ukrainian scientificresearch institute of industrial medicine, Kryvyi Rih, Ukraine In-depth analysis of diseases with the temporary disability is carried out for establish credible evidence of a causal connection between the state of health of the working and professional conditions, with the aim of developing, implementing and monitoring of the effectiveness of prophylactic measures aimed to decrease the disease and management of occupational risk. The purpose of this research is an estimation of risk of development of diseases with the temporary disability on the basis of researches of working conditions, level and structure of diseases with the temporary disability among workers, engaged in iron ore mining and processing in mining metallurgical industry of Ukraine. Professional risk of development of diseases was determined according to the international methodology for the assessment of occupational risk for health of working at the main technological processes in mining and metallurgical industry. On the basis of hygienic assessment of working conditions on indicators of harm and danger of work environment factors, severity and intensity of the working process previously determined professional risk for individual professional groups of working. The estimation of the degree of causal and effect connection of health disorders with work carried out research and the study of diseases with temporary disability. As a control group were taken workers of repair-mechanical hops. The risk of developing common diseases in workers of mining and metallurgical industry is lower than in the control group and equals to 0.127 - for underground extraction of iron ore, 0,173 for the open-pit mining of iron ore and 0,161 for metallurgical production, and the probability of the chances (to receive) of getting an occupational disease (OR) is 0,0516, 0,0061 and 0,041 respectively, which correlated with working conditions. When calculating indicators STWP found that working conditions for underground and open-pit iron ore correspond to 3 class 2 degree of hazard, and for metallurgical production – 3 class 1 degree of health hazard or permissible. An in-depth analysis of diseases and identification of the causes that leading to its increase, will allow for dynamic supervision, the monitoring of the health status of each individual worker, with the aim of timely detection of the initial manifestations of occupational diseases and mandatory conduct of rehabilitation treatment, with the aim of preserving of ability to work of employee in their profession, the individual calculation of the safe period of work and will open prospects for further scientific research aimed at the development and introduction of effective system of management of professional risk. Keywords: in-depth analysis of diseases, probability to be ill, production conditions, health conditions, proven a causal relationship. Реферат Углубленный анализ заболеваемости с временной утратой трудоспособности проводится для установления достоверно доказанной причинно-следственной связи между состоянием здоровья работающих и производственно-профессиональными условиями с целью разработки, внедрения и контроля эффективности профилактических мероприятий, которые направлены на снижение заболеваемости и управления профессиональным риском. Целью данного исследования является оценка риска развития заболеваний с временной утратой трудоспособности на основе исследований условий труда, уровня и структуры заболеваемости с временной утратой трудоспособности среди работников, занятых добычей и переработкой железной руди в горно-мнталургической отрасли Украины. Профессиональный риск развития заболеваний определяли согласно с международной методикой по оценке профессионального риска для здоровья работающих при основных технологичных процессах в горно-металлургической отрасли. На основе гигиенической оценки условий труда по показателям вредности и опасности факторов производственной среды, тяжести и напряженности трудового процесса предварительно определяли профессиональный риск для отдельных профессиональных групп работающих. Оценку степени причинно-следственной связи нарушений здоровья с работой проводили исследования и изучение заболеваемости с временной утратой трудоспособности. В качестве контрольной группы были взяты работники ремонтно-механических цехов. Риск развития общих заболеваний у работников горно-металлургической отрасли ниже, чем в контрольной группе и составляет 0,127 - для подземной добычи железной руды, 0,173 - для открытой добычи железной руды и 0,161 для металлургического производства, а отношение шансов получить профессиональное заболевание (OR) составляет 0,0516, 0,041 и 0,0061 соответственно, что коррелирует с условиями труда. При расчете показателей ЗТВП установлено, что условия труда для подземной и открытой добычи железной руды соответствуют 3 классу 2 степени вредности, а для металлургического производства – 3 классу 1 степени вредности или допустимому. Углубленный анализ заболеваемости и установление причин, приводящих к ее увеличению, позволит проводить динамическое наблюдение, мониторинг за состоянием здоровья каждого конкретного работника, с целью своевременного выявления начальных проявлений профессионального заболевания и обязательного проведения восстановительного лечения, с целью сохранения трудоспособности работника в своей профессии, расчет индивидуального безопасного срока работы и откроет перспективы для дальнейших научных исследований, направленных на разработку и внедрение эффективной системы управления профессиональным риском. Ключевые слова: углубленный анализ заболеваемости, вероятность заболеть, производственные условия, состояние здоровья, доказанная причинно-следственная связь.